KEPEMIMPINAN DAN GOVERNANCE DALAM MENGATASI KETIMPANGAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DI DAERAH 3T - Arief Tirtana (CV. ADIBA ASIHA AMIRA, 2025)
The disparity in the competence of Islamic Education (PAI) teachers in disadvantaged, frontier, and outermost (3T) regions remains a major challenge in Indonesian education. Based on data from the Ministry of Education, Culture, Research, and Technology in 2023, there is a shortage of 30% of permanent teachers, with the highest proportion in 3T regions. This disparity impacts the quality of learning and the achievement of national education goals. This article aims to examine the strategic role of educational leadership and governance in addressing this disparity. The research uses a qualitative approach with literature review and policy analysis. The results of the study indicate that transformative leadership and collaborative governance across sectors are essential for the equitable distribution of PAI teacher competencies. Key recommendations include strengthening continuous training, redistributing teachers based on regional needs, and integrating inter-ministerial programmes to improve the quality of religious education in 3T regions.